Influence of Magnetic Activity on the Determination of Stellar Parameters Through Asteroseismology - Pérez Hernández, Fernando; García, Rafael A.; Mathur, Savita; Santos, Angela R. G.; Régulo, Clara (Frontiers in Astronomy and Space Sciences, 2019)
Magnetic activity changes the gravito-acoustic modes of solar-like stars and in particular their frequencies. There is an angular-degree dependence that is believed to be caused by the non-spherical nature of the magnetic activity in the stellar convective envelope. These changes in the mode frequencies could modify the small separation of low-degree modes (i.e. frequency difference between consecutive quadrupole and radial modes), which is sensitive to the core structure and hence to the evolutionary stage of the star. Determining global stellar parameters such as the age using mode frequencies at a given moment of the magnetic activity cycle could lead to biased results. Our estimations show that in general these errors are lower than other systematic uncertainties, but in some circumstances they can be as high as $10%$ in age and of a few percent in mass and radius. In addition, the frequency shifts caused by the magnetic activity are also frequency dependent. In the solar case this is a smooth function that will mostly be masked by the filtering of the so-called surface effects. However, the observations of other stars suggest that for some of them, there is an oscillatory component with a period close to the one corresponding to the acoustic depth of the He$\,$II zone. This could give rise to a misdetermination of some global stellar parameters, such as the helium abundance. Our computations show that the uncertainties introduced by this effect are lower than the $3%$ level.